EFL learners’ perception toward the use of interactive e-book in grammar class - Rahmadani, Chikal Lexsti; Fitrawati, Fitrawati; Syarif, Hermawati (AJELP: Asian Journal of English Language and Pedagogy, 2019)
The use of multimedia has become the demand of this 21st-century education where the material used has to include more technological devices and it also supports student-oriented learning methods. The use of this kind of technology also can be applied in English lessons like grammar. In the English Department of Universitas Negeri Padang, interactive e-book has been used in the grammar class, specifically in advanced grammar class for students in the academic year 2018. This study aimed to analyze students’ perceptions toward the use of this interactive e-book in advanced grammar class. The population of this study consist of the students in the English Department from the 2018 academic year. The samples are selected through purposive sampling whereby the sample was the class that used interactive e-book in their advanced grammar class. The instrument for this study was a questionnaire, which is divided into 3 sections: interface, interactivity, and material. The data was analyzed using descriptive statistical calculation. The result of this study was students had a positive perception toward the use of interactive e-book in advanced grammar class. Hence, the students’ perceptions can be used to improve the interactive e-book used in teaching and learning process grammar.